Analisis Faktor Ekonomi, Sosial Budaya serta Profesionalisme melalui Kebijakan Imigrasi dan Regulasi terhadap Keputusan Ekspatriat untuk Bekerja di Sektor BPO (Bussiness Process Outsourcing) di Thailand (Studi pada Ekspatriat yang sedang Bekerja Di Thail - Donny Syahbana; Budi Rahayu; Enni Sustiyatik (Jurnal Ilmiah Raflesia Akuntansi, 2026)
This study aims to 1) Analyze economic factors on work decisions 2) Analyze socio-cultural factors on work decisions 3) Analyze professionalism factors on work decisions 4) Analyze regulatory policy factors on work decisions 5) Analyze economic factors through regulatory policies on work decisions 6) Analyze socio-cultural factors through regulatory policies on work decisions 7) Analyze professionalism factors through immigration policies on work decisions. This type of research is quantitative research with SEM (Structural Equation Modeling) method as its analysis method. The sample size in this study was 100 respondents, namely expatriates from Indonesia who are currently working at BPO in Thailand with a purposive sampling data collection technique. Data were collected through a questionnaire using the Google Form application. The results of this study found that economic factors have a positive and significant influence on work decisions with an O value of 0.348 and P of 0.014, socio-cultural factors have a positive and significant influence on work decisions with an O value of 0.175 and P value of 0.028, professionalism factors have a positive and significant influence on work decisions with an O value of 0.367 and P of 0.04, regulatory policy factors have a positive but insignificant influence on work decisions with an O value of 0.039 and P of 0.785, economic factors through regulatory policies have a negative and insignificant influence on work decisions with an O value of -0.13 and P value of 0.29, socio-cultural factors through regulatory policies on work decisions have a negative and insignificant influence with an O value of -0.09 and P value of 0.272, and professionalism factors through regulatory policies on work decisions have a positive and significant influence with an O value of 0.248 and P value of 0.018.